A new bond model in peridynamics theory for progressive failure in cohesive brittle materials. (January 2020) - Tong, Yue; Shen, Wanqing; Shao, Jianfu; Chen, Jueliang
Highlights: A new bond model is proposed and implemented for bond-based peridynamics theory. The new bond model considers the progressive failure and residual bond strength. The peridynamics theory is further coupled with standard finite element method. The new bond model better describes the post-peak responses of structures. Abstract: In this study, a new bond damage model is proposed in the framework of the bond-based peridynamics theory to better describe the progressive failure process in cohesive brittle materials. The new bond model is able to account for the progressive failure and residual strength of bonds. The peridynamics theory is further coupled with the classical finite element method in order to efficiently describe failure processes at a large scale of structures. Several benchmark tests concerning mode-I and mixed-mode fractures in concrete structures are studied to verify the efficiency of the coupled peridynamics-finite element method. The obtained numerical results are in good agreement with the experimental data for both overall force–displacement responses and crack propagation patterns. It is found that the new bond damage model significantly improves the prediction of progressive failure process in cohesion brittle materials with respect to the classical elastic-brittle bond model.